2017
DOI: 10.1002/2016jd026377
|View full text |Cite
|
Sign up to set email alerts
|

Examination of precipitation variability in southern Greenland

Abstract: The surface mass balance of the Greenland ice sheet has decreased in recent decades with important implications for global sea level rise. Here a climate reanalysis model is used to examine observed circulation variability and changes in precipitation across southern Greenland to gain insight into the future climate in the region. The influence on precipitation from the North Atlantic Oscillation (NAO), Atlantic Multidecadal Oscillation (AMO), Icelandic Low, Azores High, regional blocking patterns, and near‐su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 43 publications
2
18
3
Order By: Relevance
“…The glaciological and climatic characteristics of the GrIS exhibit substantial regional variability (Auger et al, ; Langen et al, ; MacGregor et al, ; Mernild et al, ; Poinar et al, ; Van As et al, ; Wilton et al, ), and we reiterate that the recent acceleration in mass loss has been most acute in western Greenland (McMillan et al, ; Mernild et al, ). We further hypothesize based on the results of Liu and Barnes () and M16 that AR moisture transport is often directed into one of two favored pathways to the west or east of Greenland depending on interactions between the North Atlantic storm track and the GrIS topography.…”
Section: Methodsmentioning
confidence: 50%
See 1 more Smart Citation
“…The glaciological and climatic characteristics of the GrIS exhibit substantial regional variability (Auger et al, ; Langen et al, ; MacGregor et al, ; Mernild et al, ; Poinar et al, ; Van As et al, ; Wilton et al, ), and we reiterate that the recent acceleration in mass loss has been most acute in western Greenland (McMillan et al, ; Mernild et al, ). We further hypothesize based on the results of Liu and Barnes () and M16 that AR moisture transport is often directed into one of two favored pathways to the west or east of Greenland depending on interactions between the North Atlantic storm track and the GrIS topography.…”
Section: Methodsmentioning
confidence: 50%
“…Atmospheric conditions tightly control both the ablation and accumulation constituents of SMB. The temporal evolution of overall GrIS SMB and the spatial patterns of SMB across the ice sheet therefore vary widely in response to short‐term weather events as well as lower frequency climate variability (Auger et al, ). Previous studies have shown that anomalous GrIS melt episodes during the warm season often occur under slow‐moving high‐pressure regimes known as “Greenland blocks,” with these blocking anticyclones favored during negative NAO conditions and often preceded by extratropical cyclones tracking to the west of Greenland (Ahlstrøm et al, ; Hanna, Jones, et al, ; Lim et al, ; McLeod & Mote, ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we measured melt layer thickness in the laboratory following Graeter et al (2018). To calculate accumulation rates at Raven-Dye-2, we use density data from a 119.6 m long firn core collected in 1997 (Bales et al, 2009) and a 19.3 m long core collected from the same location in 2015, which did not include accumulation rate data (Vandecrux et al, 2018). For this location we use the most recent density data for the near surface and the older densities for depths below the 2015 core.…”
Section: Firn Core Processing and Density Profilesmentioning
confidence: 99%
“…For each radar trace we calculate statistically significant differences (at α = 0.05) using a two-sample t test with the GreenTrACS accumulation records for each epoch and RCM accumulation rates for each common year. Additionally, we compare our Green-TrACS accumulation rates with an accumulation map kriged from 295 firn cores and 20 coastal weather stations (Bales et al, 2009; hereafter "Bales09"). We perform the same two-sample t test with the reported Bales09 uncertainty of 0.092 m w.e.…”
Section: Model Comparisonmentioning
confidence: 99%
See 1 more Smart Citation